Birkhoff Center of a Quotient of Almost Distributive Fuzzy Lattices - Alaba, Brhanu Asaye; Taye, Mihret Alamneh; Dejen, Gerima Tefera (Journal of Informatics and Mathematical Sciences, 2019)
The concept of a fuzzy congruence relation is introduced, and we also prove quotient isomorphism in Almost Distributive Fuzzy lattice.